Water histories of South Asia: the materiality of liquescence - Ray, Sugata; Venugopal, Maddipati (Routledge, 2020)
"This book surveys the intersections between water systems and the phenomenology of visual cultures in early modern, colonial, and contemporary South Asia from the 16th century to the present. Bringing together contributions by art and architecture historians, artists, architects, geographers, maritime historians, and environmental activists from India, Europe, and the United States, the volume situates water in an expansive relational domain. It covers disciplines as diverse as literary studies, environmental humanities, sustainable design, urban planning, and media studies. The chapters explore the ways in which material cultures of water generate technological and aesthetic acts of envisioning geographies and make an intervention within political, developmental, and cultural discourses. A critical interjection in the sociologies of water in the subcontinent, the book brings art history into conversation with current debates on climate change, and examines the artistic, architectural, engineering, religious, scientific, and environmental facets"--
Includes bibliographical references and index
Keywords: South Asia -- Civilization; South Asia -- Environmental conditions -- History; Aufsatzsammlung; Geschichte; Wasserbau; Wasserwirtschaft; Indien